Luteolin reduces the invasive potential of malignant melanoma cells by targeting β3 integrin and the epithelial-mesenchymal transition - Ruan Jun-shan; Liu Yu-ping; Zhang Lei; Yan Ling-geng; Fan Fang-tian; Shen Cun-si; Wang Ai-yun; Zheng Shi-zhong; Wang Shao-ming; Lu Yin (Acta Pharmacologica Sinica, 2016)
Aim: To investigate whether luteolin, a highly prevalent flavonoid, reverses the effects of epithelial-mesenchymal transition (EMT) in vitro and in vivo and to determine the mechanisms underlying this reversal. Methods: Murine malignant melanoma B16F10 cells were exposed to 1% O2 for 24 h. Cellular mobility and adhesion were assessed using Boyden chamber transwell assay and cell adhesion assay, respectively. EMT-related proteins, such as E-cadherin and N-cadherin, were examined using Western blotting. Female C57BL/6 mice (6 to 8 weeks old) were injected with B16F10 cells (1×106 cells in 0.2 mL per mouse) via the lateral tail vein. The mice were treated with luteolin (10 or 20 mg/kg, ip) daily for 23 d. On the 23rd day after tumor injection, the mice were sacrificed, and the lungs were collected, and metastatic foci in the lung surfaces were photographed. Tissue sections were analyzed with immunohistochemistry and HE staining. Results: Hypoxia changed the morphology of B16F10 cells in vitro from the cobblestone-like to mesenchymal-like strips, which was accompanied by increased cellular adhesion and invasion. Luteolin (5−50 μmol/L) suppressed the hypoxia-induced changes in the cells in a dose-dependent manner. Hypoxia significantly decreased the expression of E-cadherin while increased the expression of N-cadherin in the cells (indicating the occurrence of EMT-like transformation), which was reversed by luteolin (5 μmol/L). In B16F10 cells, luteolin up-regulated E-cadherin at least partly via inhibiting the β3 integrin/FAK signal pathway. In experimental metastasis model mice, treatment with luteolin (10 or 20 mg/kg) reduced metastatic colonization in the lungs by 50%. Furthermore, the treatment increased the expression of E-cadherin while reduced the expression of vimentin and β3 integrin in the tumor tissues. Conclusion: Luteolin inhibits the hypoxia-induced EMT in malignant melanoma cells both in vitro and in vivo via the regulation of β3 integrin, suggesting that luteolin may be applied as a potential anticancer chemopreventative and chemotherapeutic agent.